Catalysts and processes for depolymerization of polymer waste

By using a catalyst that combines acidic compounds with non-porous support in the chemical recycling of plastic waste, the problem of mixing different types of plastics is solved, and the heating process is difficult to control, achieving high-efficiency and low-energy-consuming plastic decomposition is achieved, high-purity gas and liquid products are produced, and the catalyst can be reused.

JP2025510516APending Publication Date: 2025-04-15BASELL POLIOLEFINE ITALIA SRL
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024550578
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to control the heating process due to the mixing of different types of plastics when chemical recycling of plastic waste, which increases energy consumption and reduces the quality and yield of products.

Method used

A catalyst is used that is bound by an acidic compound with a nonporous solid support and deposited by a coating agent for catalyzing the decomposition of plastic waste. The catalyst includes acidic active substances such as aluminum/silicon mixed oxides, aluminum oxides or zeolites. By combining with non-porous support materials such as sand, glass beads or metal particles, a catalyst with high heat conduction properties is formed.

Benefits of technology

High purity decomposition products, high gas fraction content and low carbide generation are achieved, and the catalyst can be reused to save resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510516000012
    Figure 2025510516000012
  • Figure 2025510516000013
    Figure 2025510516000013
  • Figure 2025510516000001
    Figure 2025510516000001
Patent Text Reader

Abstract

A catalyst for depolymerization of waste polymers, comprising an acidic component deposited on a solid support with the aid of a coating agent, and a process for depolymerization of waste polymers using said catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS Not applicable.

[0002] The present disclosure relates to the depolymerization of waste polymers. More specifically, the present disclosure relates to a catalyst for depolymerization of waste polymers, comprising an acidic component deposited on a solid support with the aid of a coating agent, and a catalytic process for depolymerization of waste polymers using the catalyst. [Background technology]

[0003] Plastics include a variety of synthetic and semi-synthetic materials that use polymers as their main components. Their plasticity allows them to be molded, extruded, or pressed into solid objects of various shapes. This adaptability, combined with a variety of other properties such as light weight, durability, and low production costs, has led to their widespread use. The production of plastics has increased dramatically over the past decades. At the same time, the increasing amount of plastics poses environmental problems, since most plastics are resistant to natural degradation processes. As such, the material can persist for centuries or more, filling up landfills and even appearing in the food chain as microplastics.

[0004] Therefore, efforts are being made to improve the recycling of polymer waste. Current recycling procedures mainly rely on mechanical and chemical recycling. In mechanical recycling, plastics are mechanically transformed without changing their chemical structure, making them available for the production of new materials. The general mechanical recycling process includes collecting the polymer waste, sorting the polymer waste into different types of plastics and colors, baling the plastic waste by pressing or crushing, washing and drying the polymer waste, and reprocessing the polymer waste into pellets by agglomerating, extruding and cooling the plastics to obtain recycled raw materials that can then be molded into new articles.

[0005] During chemical recycling, plastics are reprocessed and their structure and chemistry modified so that they can be used as raw materials for various industries or as basic inputs or feedstocks for the production of new polymer products. Chemical recycling typically involves collecting plastic waste and then heating it to break down the polymers to obtain monomers that are then used to remanufacture polymers or to produce other synthetic chemicals.

[0006] In practice, different types of polymer waste are often collected together, which makes chemical recycling particularly difficult, as the mixture of different polymers makes the heating process difficult to control, resulting in high energy costs and reduced yield and quality of the resulting products.

[0007] In this regard, considerable efforts have been made to improve the process of polymer depolymerization.

[0008] Chemical recycling of polymer waste dates back to the 1970s. Patent Document 1 describes a method for treating rubber and plastic waste, which includes a series of steps: (i) heating and melting rubber and plastic waste in an extruder at a temperature T1 to knead and melt the waste, and extruding the molten waste in a molten state into a decomposition zone; (ii) heating the molten waste in the extruder at a temperature T2 in the decomposition zone to form a decomposition product, and sending the decomposition product to a carbonization zone; (iii) heating the decomposition product in the carbonization zone at a temperature lower than the heating temperature T2 in the decomposition zone to gasify the product by carbonization; and (iv) sending the carbonization product to a cooling zone for cooling the carbonization product to separate liquid substances from gaseous substances.

[0009] US Pat. No. 5,399,633 refers to a process for utilizing plastic polymers in which the latter are contacted with a catalyst at high temperature and the reaction products resulting from the resulting gas phase are at least partially condensed.

[0010] Patent Document 3 provides technology relating to polymer depolymerization, in particular, a method and system for decrosslinking polyacrylate salt-based polymers and other polymers by ultrasonicating an aqueous superabsorbent polymer (SAP) hydrogel, and a composition made by decrosslinking polyacrylate salt-based polymers and other polymers to produce polyacrylic acid (PAA) from superabsorbent polymer (SAP).

[0011] Patent document 4 presents a method for depolymerizing plastics, which includes the steps of a) introducing a raw material containing plastics, b) mixing the raw material containing plastics with a catalyst to obtain a reaction mixture, and c) heating the reaction mixture to obtain a product using the catalyst being halloysite.

[0012] US Patent No. 5,399,633 relates to a process for depolymerizing plastics, the process including: a) mixing solid plastic particles with a solvent to produce a heterogeneous reaction mixture; b) passing the heterogeneous reaction mixture through a first section of a first heat exchanger to preheat the heterogeneous reaction mixture; c) passing the preheated heterogeneous reaction mixture through a heating zone of a heating chamber; d) heating the heterogeneous mixture in the heating zone of the heating chamber to a reaction temperature sufficient to initiate conversion of the heterogeneous reaction mixture to a homogeneous reaction solution comprising a liquefied reaction product; e) passing the homogeneous reaction solution through a second section of the first heat exchanger to cool the homogeneous reaction solution; and f) sending the homogeneous reaction solution to a precipitation tank to convert the liquefied reaction product to a solid reaction product and precipitate from the cooled homogeneous reaction solution. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] U.S. Patent No. 3,984,288 [Patent Document 2] German patent no. 198 22 568 [Patent Document 3] U.S. Patent Application Publication No. 2021 / 0054161 [Patent Document 4] International Publication No. 2021 / 048185 [Patent Document 5] International Publication No. 2020 / 061521 Summary of the Invention [Problem to be solved by the invention]

[0014] Considering the above and the ever-increasing demand for polymers, there remains a need for an efficient recycling process for polymer waste, which is solved by the present disclosure, which proposes a catalyst for the depolymerization of polymer waste and a process for recycling polymer waste by depolymerization using said catalyst. [Means for solving the problem]

[0015] In one aspect, the present disclosure provides a catalyst for depolymerization of polymer waste, the catalyst comprising as an active component an acidic compound deposited on a particulate non-porous support with the aid of a coating agent.

[0016] In one embodiment, the particulate non-porous support is selected from the group consisting of sand, glass beads and metal particles.

[0017] In one embodiment, the acidic compound is selected from the group consisting of Al / Si mixed oxides, Al2O3, aluminosilicates, silica and zeolites.

[0018] In one embodiment, the coating agent is selected from the group consisting of oils, inorganic hydrogels, or combinations thereof.

[0019] In one embodiment, the active compound is included in the catalyst in an amount of 0.5 to 6.0% by weight, preferably 1.0 to 4.0% by weight, based on the total weight of the catalyst.

[0020] In another aspect, the present disclosure provides a process for depolymerization of waste polymers, the process comprising: (a) providing a feedstock of waste polymers; (b) mixing the feedstock with a catalyst of the present disclosure; (c) pyrolyzing the mixture; (d) collecting a gaseous fraction produced during pyrolysis; and (e) separating the collected gaseous fraction to obtain a gaseous depolymerization product and a liquid depolymerization product.

[0021] In one embodiment, the process further comprises distilling the liquid depolymerization product.

[0022] In one embodiment, the polymer waste is a polymer waste consisting of or containing a plastic material selected from the group including or consisting of polyethylene (PE), polypropylene (PP), polystyrene (PS), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polyamide (PA), polyurethane (PU), polyacrylonitrile (PAN), and polybutylene (PB), and mixtures thereof.

[0023] In a preferred embodiment, the gas content in the depolymerization product after step (e) is preferably greater than 30 wt.%, more preferably greater than 50 wt.%, especially greater than 70 wt.%, based on the combined weight of the gaseous depolymerization product and the liquid depolymerization product.

[0024] In one embodiment, the gaseous depolymerization is carried out using a process having the general formula C, based on the total weight of the gaseous depolymerization product after step (e) of the process of the present disclosure. n H 2n The content of the compound (n=2 to 4) is at least 50% by weight, preferably at least 60% by weight, particularly preferably at least 65% by weight.

[0025] In one embodiment, the resulting liquid depolymerization product has a content of olefinic compounds, expressed as Bromine Number (grams of bromine per 100 grams of sample), determined according to ASTM D1159-01, of less than 150, preferably between 10 and 100, more preferably between 15 and 80, even more preferably between 20 and 70, in particular between 25 and 100, and / or the 1H-NMR spectrum of the resulting liquid depolymerization product exhibits less than 10 mol %, preferably less than 5 mol %, in particular not more than 3 mol % of olefinic protons.

[0026] In one embodiment, the content of aromatics in the resulting liquid depolymerized product is less than 10 mol %, preferably less than 5 mol %, in particular less than or equal to 3 mol %, the content of aromatics being measured as the content in mol % of aromatic protons as determined by H-NMR spectroscopy.

[0027] In a preferred embodiment, the waste polymer feedstock for depolymerization has the following characteristics: (a) a polyolefin content, in particular a total content of polypropylene (PP) and polyethylene (PE), of more than 50 wt.-%, preferably more than 60 wt.-%, more preferably more than 70 wt.-%, in particular more than 80 wt.-%, in particular more than 90 wt.-%, based on the total weight of the waste polymer feedstock; (b) a total ash content, determined as the residue after heating the waste polymer feedstock at 800° C. in air for 120 hours, of less than 15 wt.-%, preferably less than 10 wt.-%, more preferably less than 10 wt.-%. (c) a bulk density of the polymer waste feedstock when present in shredded form of 70-500 g / L, preferably 100-450 g / L, and of 300-700 g / L when the polymer waste feedstock is in pellet form, each bulk density being determined according to DIN 53466; and (d) a total volatile matter (TV) content measured as the weight loss of a 10 g sample at 100° C. after 2 hours at 200 mbar of less than 5%, preferably less than 3%.

[0028] Certain embodiments of the present disclosure will now be described with reference to the accompanying drawings, in which like reference numerals refer to like elements, and in which it is to be understood that the accompanying drawings are illustrative of various implementations described herein and are not intended to limit the scope of the various technologies described herein. [Brief description of the drawings]

[0029] [Figure 1] FIG. 1 is a flow chart illustrating a general process according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a flow chart illustrating an example operation according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The disclosure herein relates generally to catalysts and processes for the depolymerization of plastic waste.

[0031] Catalyst for depolymerization

[0032] In a first aspect of the present disclosure, a catalyst for depolymerization of polymer waste is provided, which comprises as an active component an acidic compound deposited on a particulate non-porous support with the aid of a coating agent.

[0033] Surprisingly, it has been found that the catalysts of the present disclosure are capable of producing high purity depolymerization products with high gaseous fraction content and low char formation. Furthermore, it has been found that the catalysts of the present disclosure are easily separable from the solid residues of the depolymerization process, allowing for multiple uses.

[0034] Without being bound by theory, the above performance may be due to the fact that the catalyst effectively supports the heat transfer that occurs during the pyrolysis of polymer waste.

[0035] To aid in efficient pyrolysis and depolymerization of the polymer waste, the catalyst of the present disclosure is in particulate form. Particulate non-porous supports selected from the group consisting of sand, glass beads, and metal particles are preferred. The particulate non-porous supports may have any shape, such as spherical, cylindrical, or any non-homogeneous shape. The supports used in the catalyst of the present invention are not only particulate, but also non-porous. Non-porous in the sense of the present disclosure is understood as being impermeable to gases, such as air, or liquids, such as water. In order to design the catalyst of the present disclosure specifically to be mixed with the polymer waste undergoing depolymerization, the supports preferably have an average particle size D50 of 0.2-20 mm, preferably 0.5-10 mm, more preferably 1-8, and most preferably 1-6 mm, determined according to sieve analysis in accordance with ISO3310-1 / ASTM E11. An example of a sieving device that can be used is the Retsch test sieve device with a woven wire mesh sieve (Φ125 mm-20 μm).

[0036] Sand is a preferred type of non-porous particulate support and preferably has the following particle size distribution: [Table 1]

[0037] The acidic compounds of the catalyst of the present disclosure are preferably selected from the group consisting of Al / Si mixed oxides, Al2O3, aluminosilicates, silica and zeolites. The Al / Si mixed oxides particularly preferred in the present disclosure refer to materials comprising a mixture of Al2O3 and SiO2 with a neutral structure.

[0038] The zeolites referred to in this disclosure have the general structure M n +x / n[AlO2]-x(SiO2) y ]+zH2O, where n is the charge of the cation M, typically an alkali metal or alkaline earth metal or a hydrogen ion, preferably H + , Na + , Ca2 + , K + and Mg2 + It is to be understood that zeolites are crystalline microporous aluminosilicates built up from corner-sharing SiO4- and AlO4-tetrahedra with z being an ion selected from the group consisting of z, z defining the number of water molecules incorporated in the crystal structure. Zeolites differ from Al / Si mixed oxides by their well-defined pore structure and ionic properties. In a particularly preferred embodiment, the zeolite used as acidic compound is selected from the group consisting of zeolite Y, zeolite beta, zeolite A, zeolite X, zeolite L and mixtures thereof, in particular zeolite Y and zeolite beta. The listed zeolites are well known and commercially available. Zeolites in which the metal ion M is replaced by hydrogen are particularly preferred. Other specific examples of suitable zeolite-type components for use in the present disclosure include, but are not limited to, ZSM-5, ZSM-11, ZSM-22, ZSM-23, ZSM-35, ZSM-48, ZSM-50, TS-1, TS-2, SSZ-46, MCM-22, MCM-49, FU-9, PSH-3, ITQ-1, EU-1, NU-10, silicalite-1, silicalite-2, boralite-C, boralite-D, BCA, and mixtures thereof.

[0039] In a particularly preferred embodiment, the acidic compound is an Al / Si mixed oxide. The composition of the Al / Si mixed oxide used as the support can be adjusted as necessary. However, particularly favorable depolymerization results are obtained when the acidic compound contains certain amounts of Al2O3 and SiO2. Thus, in a preferred embodiment, the acidic compound contains Al2O3 in an amount of 20-99 wt.%, preferably 30-80 wt.%, in particular 40-70 wt.%, based on the total weight of the acidic compound. Furthermore, the acidic compound contains SiO2 in an amount of 1-80 wt.%, preferably 20-70 wt.%, in particular 30-60 wt.%, based on the total weight of the acidic compound.

[0040] Surprisingly, it has been found that the results of the depolymerization process can be further improved if the acidic compound comprises an excess of Al2O3 relative to SiO2. Thus, in a preferred embodiment, the acidic compound comprises an excess of Al2O3 relative to SiO2. Further preferred are embodiments in which the weight ratio of Al2O3 to SiO2 in the acidic compound is 99:1 to 30:70, preferably 9:1 to 3:2, in particular 4:1 to 3:2.

[0041] Measurement of the SiO2 and Al2O3 content of acidic compounds can be performed by atomic emission spectroscopy using inductively coupled plasma (ICP-AES).

[0042] The coating agent used in the catalyst of the present disclosure is preferably selected from the group consisting of oil, inorganic hydrogel, or a combination thereof. As an inorganic hydrogel, silica hydrogel is preferred. As for the oil used as the coating agent, a white mineral oil, preferably based on isoparaffin, and free of aromatics, is preferred. In a preferred embodiment, the oil used has a kinematic viscosity at 20°C of 140-180 mm 2 / s, preferably 150-170 mm 2 / s and / or a kinematic viscosity at 40°C of 40 to 80 mm 2 / s, preferably 50-70 mm 2 / s and / or a kinematic viscosity at 100°C of 5 to 15 mm 2 / s, preferably 7 to 10 mm 2 / s. Kinematic viscosity can be determined according to ISO 3104.

[0043] The preferred amount of the coating agent is in the range of 1-300%, preferably 2-150% by weight, more preferably 5-100% by weight, and most preferably 10-80% by weight, based on the amount of the acidic compound. In the case of a hydrogel, the amount used is expressed as a dry weight.

[0044] In a further preferred embodiment, the active compound is included in the catalyst of the present disclosure in an amount of 0.5-6 wt. %, preferably 2-4 wt. %, based on the total weight of the catalyst.

[0045] The catalyst of the present disclosure is preferably obtained by mixing a particulate non-porous carrier with a coating agent, and then adding an acidic compound in powder form to the resulting mixture. The mixture may be optionally heat-treated to obtain the catalyst. The heat treatment may be carried out, for example, at a temperature of 100 to 600°C. In a preferred embodiment, the particulate non-porous carrier is subjected to a drying process before being mixed with the coating agent.

[0046] Thus, in a preferred embodiment, the present disclosure relates to a catalyst obtained by a process comprising the steps of: (a) mixing a particulate non-porous support with a coating agent; and (b) adding an acidic compound in powder form to the mixture of step (a).

[0047] In a particularly preferred embodiment, the catalyst is characterized as follows: (a) sand as a particulate non-porous support, (b) Al / Si mixed oxide or zeolite as the acidic compound, and (c) mineral oil or silica hydrogel as the coating agent.

[0048] The catalyst of the present disclosure, preferably the catalyst in which component (c) is selected from hydrogels, can surprisingly be reactivated by heating, which allows multiple use and saves resources. Thus, in a preferred embodiment, the catalyst is reactivatable by heat treatment. The heat treatment is preferably carried out at a temperature of 500-900°C, in particular 550-900°C, most preferably 600-850°C. In some embodiments of the present disclosure, the heat treatment is preferably carried out in an oxidizing atmosphere, such as air or oxygen. The treatment time can be selected by experimental investigation to find the best balance between catalytic activity and energy consumption. In this respect, the carbon residue concentration on the catalyst is a parameter to be considered. Preferably, the carbon residue of the regenerated catalyst is less than 20% by weight of the catalyst, preferably less than 15%, more preferably less than 10%, most preferably less than 5%. Treatment times of 0.5-100 hours, preferably 1-20 hours, more preferably 2-10 hours are possible, without excluding other treatment times.

[0049] Depolymerization

[0050] In another aspect, the present disclosure provides a process for depolymerization of plastic waste, the process comprising the steps of: (a) providing a feedstock of plastic waste; (b) mixing the feedstock with a catalyst of the present disclosure; (c) pyrolyzing the mixture; (d) collecting a gaseous fraction produced during pyrolysis; and (e) separating the collected gaseous fraction to obtain a gaseous depolymerization product and a liquid depolymerization product.

[0051] As already explained, the catalyst used is preferably separated from the solid contents remaining after the depolymerization process and reintroduced into the process.

[0052] The recovered gaseous fraction may be separated by condensation into a liquid depolymerization product and a gaseous depolymerization product, which may then be further processed.

[0053] The process of the present disclosure may produce little or no char. Thus, in a preferred embodiment, the residue of the depolymerization process of the present disclosure has a char content of less than 5 wt.%, preferably less than 2 wt.%, based on the total weight of the product.

[0054] The resulting liquid depolymerization product may be further separated. Thus, the process of the present disclosure may further comprise a step of distilling the liquid depolymerization product.

[0055] Surprisingly, it has been found that the process of the present disclosure can result in a depolymerized product with a high gas content. In a preferred embodiment, the gas content in the depolymerized product after step (e) is preferably greater than 30 wt.%, more preferably greater than 50 wt.%, especially greater than 70 wt.%, based on the combined weight of the gaseous depolymerized product and the liquid depolymerized product.

[0056] The gaseous fraction of the depolymerization product is further characterized by a high content of monomeric olefinic C2-C4 compounds that are particularly useful for further processing, such as for example the production of polymers. Due to the high amount of such compounds produced during depolymerization, the gaseous depolymerization product may be used directly as a feedstock for a cracking process and subsequent polymerization. The gaseous product, including light olefins and light alkanes, can be transferred to a downstream cracker, for example by passing through an oven, to produce a polymerization-grade monomer stream. Other by-products, such as ethane, propane, and butane, can be cracked in an oven. Thus, the normally necessary step of processing the product obtained after depolymerization to obtain the desired monomers can be omitted, thus saving valuable energy and reducing CO2 emissions.

[0057] Polymer waste raw material

[0058] The process of the present disclosure has been found to be suitable for recycling a variety of waste polymer materials, particularly waste plastic materials. The waste polymer feedstock used in the process of the present disclosure can include virtually any polymeric material, particularly those formed from synthetic polymers. Non-limiting examples include polyolefins such as polyethylene, polypropylene, polystyrene, polyethylene terephthalate (PET), polyvinyl chloride (PVC), polyamide, polycarbonate, polyurethane, polyester, natural and synthetic rubber, tires, filled polymers, composites and plastic alloys, plastics dissolved in solvents, and the like. During the development of the process of the present disclosure, it was surprisingly found that other hydrocarbon materials can also be used as waste polymer feedstocks. These hydrocarbons include biomass, bio-oil, petroleum, and the like. Thus, although this specification is primarily directed to the depolymerization of polymer feedstocks, it should be understood that the process of the present disclosure is applicable to and encompasses the use of other hydrocarbons. Where the production of light gas olefins is desired, a plastic feedstock consisting primarily of or containing a majority of polyolefins may be preferred. A variety of different mixtures of plastic and hydrocarbon materials can be used without limitation.

[0059] The polymer waste feedstock may consist of one type of polymer waste or may be a mixture of two or more different types of polymer waste. The polymer waste feedstock may be provided in a variety of different forms. In smaller scale operations, the polymer waste feedstock may be in the form of a powder. In larger scale operations, the polymer waste feedstock may be in the form of pellets, such as those having a particle size of 1-20 mm, preferably 2-10 mm, more preferably 2-8 mm, or in the form of chopped flakes and / or small pieces of film, preferably having a particle size of 1-20 mm. In the context of this disclosure, having a particle size within a specified range means that 90% by weight of the particles have a particle size that is within the specified range. Particle size may be measured by sieving or using a Beckman Coulters LS13320 laser diffraction particle size analyzer.

[0060] Polymer waste consists mainly of plastic materials and is generally named after the type of polymer that forms the main component of the polymer waste. Preferably, the polymer waste used as a feedstock in the process of the present disclosure contains more than 25% by weight of polymer material, preferably more than 40% by weight, more preferably more than 50% by weight of the total weight. Other components in the polymer waste feedstock may be additives such as, for example, fillers, reinforcing agents, processing aids, plasticizers, pigments, light stabilizers, lubricants, impact modifiers, antistatic agents, inks, antioxidants, etc.

[0061] The polymer waste materials used in the process of the present disclosure preferably include polyolefins and polystyrenes, such as high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), ethylene-propylene-diene monomer (EPDM), polypropylene (PP), and polystyrene (PS). Polymer waste materials comprising mixtures of polyolefins and polystyrenes are particularly preferred.

[0062] Other waste polymers such as polyvinyl chloride, polyvinylidene chloride, polyethylene terephthalate, polyurethane (PU), acrylonitrile-butadiene-styrene (ABS), nylon and fluorinated polymers can also be used in the process of the present disclosure. When present in the waste polymer, these polymers are preferably present in an amount of less than 50% by weight, preferably less than 30% by weight, more preferably less than 20% by weight, and even more preferably less than 10% by weight, based on the total weight of the dry weight of the waste polymer feedstock.

[0063] Preferably, the polymer waste comprises one or more thermoplastic polymers and is substantially free of thermosetting polymers, where substantially free in this context means that the thermosetting polymer content is less than 15% by weight, preferably less than 10% by weight, and even more preferably less than 5% by weight, based on the polymer waste feedstock.

[0064] The polymer waste material used in the process of the present disclosure is preferably selected from the group consisting of single plastic waste, on-spec or off-spec single virgin plastic, mixed plastic waste, rubber waste, decomposition oil residue, used oil, biomass or mixtures thereof. Single plastic waste, off-spec single virgin plastic, mixed plastic waste, rubber waste or mixtures thereof are preferred. Off-spec single virgin plastic, mixed plastic waste or mixtures thereof are particularly preferred.

[0065] The polymer waste may contain limited amounts of non-pyrolyzable components as foreign matter, such as water, glass, stones, metals, etc. By "limited amounts" it is preferably meant an amount less than 50% by weight, preferably less than 20% by weight, more preferably less than 10% by weight, based on the total weight of the dry polymer waste feedstock.

[0066] The waste polymer may optionally be extruded prior to use as a feedstock in the process of the present disclosure. In a preferred embodiment, the waste polymer is pelletized and the pellets are used as a feedstock in the process of the present disclosure. In another preferred embodiment, the waste polymer is used in a molten state, for example at a temperature of 200°C to 300°C.

[0067] Particularly preferred types of polymer waste materials used as feedstock in the process of the present disclosure are characterized by the following features:

[0068] i) a total content of volatiles (TV), measured as the weight loss of a 10 g sample after 2 hours at 100° C. and 200 mbar pressure, of less than 5%, preferably less than 3%, more preferably less than 2%, in particular less than 1%;

[0069] ii) the polymer waste is shredded, optionally compressed, polymer waste and has a bulk density of 70-500 g / L, preferably 100-450 g / L, or the polymer waste is in pellet form and has a bulk density of 300-700 g / L, the bulk density being measured according to DIN 53466;

[0070] iii) the content of polyolefins in the polymer waste, in particular the content of polypropylene (PP) and / or polyethylene (PE), is greater than 50% by weight, preferably greater than 60% by weight, more preferably greater than 70% by weight, in particular greater than 80% by weight, in particular greater than 90% by weight, based on the total weight of the polymer waste raw material;

[0071] iv) the amount of polar polymer contaminants in the polymer waste is less than 10% by weight, preferably less than 5% by weight, more preferably less than 3% by weight, based on the total weight of the polymer waste;

[0072] v) the amount of cellulose, wood and / or paper in the polymer waste is less than 10% by weight, preferably less than 5% by weight, more preferably less than 3% by weight, based on the total weight of the polymer waste;

[0073] vi) a total chlorine content of less than 1.0 wt.%, preferably less than 0.5 wt.%, more preferably less than 0.1 wt.%, based on the total weight of the polymer waste;

[0074] vii) The total ash content of the polymer waste feedstock, determined as the residue after heating the polymer waste at 800°C in air for 120 hours, is less than 15% by weight, preferably less than 10% by weight, more preferably less than 5% by weight, and most preferably less than 3% by weight. In another preferred embodiment, the ash content is between 0.01 and 2% by weight, preferably between 0.02 and 1.5% by weight, and more preferably between 0.05 and 1.0% by weight.

[0075] In a preferred embodiment of the present disclosure, the waste polymer material used as a raw material in the process of the present disclosure is defined by upper limits of trace components, constituents or impurities expressed in weight percent. The lower limits of the amount of these components, constituents or impurities in the preferred waste polymer material are preferably below the detection limit, or the lower limit is 0.001% by weight or 0.01% by weight or 0.1% by weight, respectively.

[0076] Many techniques are known for separating materials in polymer waste streams. Moving beds, drums and screens, and air separators are used to fractionate materials according to size, weight, and density. Advanced sorting of plastic waste by spectroscopy (MIR, NIR [near infrared]), X-ray, or fluorescence spectroscopy provides high quality plastic waste streams with high polyolefin content.

[0077] Automated sorting technologies for waste plastics include dry sorting technologies, electrostatic sorting technologies, mechanical sorting methods (including centrifugal force, specific gravity, elasticity, particle shape, selective crushing, and mechanical properties), as well as wet sorting technologies (e.g., sinking and flotation sorting methods), and chemical sorting methods.

[0078] Suitable raw materials for use in the process of the present disclosure can be obtained by applying any of the known sorting techniques, for example as summarized in B. Ruj et al: Sorting of plastic waste for effective recycling, Int. J. Appl. Sci. Eng. Res 4, 2015, 564-571.

[0079] Reactor

[0080] The depolymerization process according to the present disclosure can be carried out in a reactor including (a) a feeding device for introducing polymer waste and a catalyst into the reactor, (b) a pyrolysis device equipped with a heating unit, a gas discharge unit and a solid discharge unit, and (c) a condensation device.

[0081] Preferably, gas discharge units are distributed throughout the pyrolysis device and are provided with an outlet for discharging the gaseous fraction of the depolymerization and an inlet for introducing a wash gas into the pyrolysis device.

[0082] In a preferred embodiment, the reactor may comprise two or more pyrolysis units.

[0083] The polymer waste feedstock and catalyst are introduced into the pyrolysis unit through at least one feeder and then heated to achieve depolymerization. The gaseous fraction produced during depolymerization is discharged through the outlet of the gas discharge unit and conveyed to a condensation unit for further processing. The solid residue of the depolymerization, if any, is discharged through a solid discharge unit. A washing gas for washing the gas discharge unit and the pyrolysis unit may be introduced through the inlet of the gas discharge unit.

[0084] In a preferred embodiment, the gas discharge unit is equipped with a filter membrane to ensure that the gaseous fraction is free of solids after being discharged from the pyrolysis device. The gas discharge unit is preferably made of metal or ceramic particle or fiber material.

[0085] The pyrolyzer is preferably further equipped with a screw for uniformly mixing the polymer waste in the pyrolyzer throughout the depolymerization. The residence time of the solids in the pyrolyzer could be clearly defined by adjusting the rotation speed of the screw. The pyrolyzer is preferably operated at a temperature of 350-550°C.

[0086] The gaseous fraction discharged from the depolymerization is conveyed to a condenser to obtain a liquid depolymerized product and a gaseous depolymerized product. In a preferred embodiment, the condenser includes a plurality of condensers preferably operated at different temperatures. The temperature of the condenser may be set according to the boiling point of the condensate.

[0087] depolymerization products

[0088] The disclosed process provides a surprisingly highly selective depolymerization product: the gaseous fraction produced during pyrolysis is separated, for example, by condensation, into liquid and gaseous depolymerization products.

[0089] liquid depolymerization products

[0090] The resulting liquid depolymerized product exhibits a surprisingly low content of aromatic compounds, and in particular a surprisingly low content of polycyclic aromatic compounds and asphaltanes. Thus, the liquid depolymerized product obtained by the process of the present disclosure is characterized by a low content of aromatic and olefinic components and a high purity.

[0091] Preferably, the content of aromatic compounds in the resulting liquid depolymerization product is less than 10 mol %, preferably less than 5 mol %, in particular equal to or less than 3 mol %, the content of aromatic components being measured as the content in mol % of aromatic protons as determined by 1H-NMR spectroscopy.

[0092] In addition, the liquid depolymerized product obtained by the depolymerization process of the present disclosure is characterized by a low content of olefinic compounds, the content of olefinic compounds in the liquid depolymerized product is preferably less than 7 mol%, more preferably less than 5 mol%, and even more preferably less than 3 mol%, based on the total number of hydrocarbon protons, and the content of olefinic compounds is determined based on the content of olefinic protons as determined by 1H-NMR spectroscopy.

[0093] Another measure of the content of double bonds in a given sample is the Bromine number (BrNo.), which indicates the degree of unsaturation. In a preferred embodiment, the liquid depolymerized product obtained by the process of the present disclosure has a Bromine number, expressed as grams of bromine per 100 grams of sample, of less than 150, preferably 10-100, more preferably 15-80, even more preferably 20-70, and especially 25-100, measured according to ASTM D1159-01.

[0094] The liquid depolymerization product obtained by the process of the present disclosure preferably has a boiling point range of 30 to 650° C., more preferably 50 to 250° C. By separation techniques such as distillation, the depolymerization product can be separated into hydrocarbon fractions of different boiling point ranges, for example, a light naphtha fraction containing mainly C5 and C6 hydrocarbons with a boiling point range of 30° C. to 130° C., a C6 to C8 hydrocarbon fraction with a boiling point range of 130° C. to 220° C., and a light naphtha fraction containing mainly C5 and C6 hydrocarbons with a boiling point range of 130° C. to 220° C.12 Heavy naphtha fraction containing mainly hydrocarbons, C9-C with a boiling range of 220°C to 270°C 17 It may be separated into a kerosene fraction containing primarily hydrocarbons, or other higher boiling fractions such as diesel fuel, fuel oil, or hydrowax.

[0095] Even more surprisingly, it has been found that the liquid depolymerization product contains little or no solid residue, and in a preferred embodiment, the liquid depolymerization product upon evaporation has a residue content of 5 ppm(w) or less, as determined according to ASTM D381.

[0096] Gaseous depolymerization products

[0097] The resulting gaseous depolymerization product exhibits a surprisingly low content of low molecular weight hydrocarbons, such as methane or ethane. Rather, it has been surprisingly found that the gaseous depolymerization product contains unusually high amounts of higher olefins, such as ethylene, propylene, and butenes, which are typically desired for polyolefin production. Thus, the gaseous depolymerization product obtained by the process of the present disclosure exhibits a high content of either ethylene, propylene, and butenes, and / or a high content of saturated low molecular weight hydrocarbons, particularly olefins of the general formula C n H 2n+2 (wherein n is a real number in the range of 1 to 4) is characterized by a low content of hydrocarbons.

[0098] In a preferred embodiment, the gaseous depolymerization product of the disclosed process is characterized by a methane content of at most 6 wt.-%, preferably at most 4 wt.-%, more preferably at most 3 wt.-%, most preferably at most 2 wt.-%, in particular at most 0.5-1.5 wt.-%, based on the total weight of the gaseous depolymerization product after step (e) of the disclosed process.

[0099] Surprisingly, the gaseous depolymerization products obtained by the process of the present disclosure contain, in particular, n H 2nIt was found that the gaseous fraction contained a large amount of low molecular weight olefin compounds of the type (n=2-4). Thus, the gaseous fraction can be directly used as a feedstock for further processing in a downstream cracker, e.g., a feed gas compressor to obtain a purified monomer stream, which can then be used for the production of polymers, thus avoiding the energy-intensive stream cracking ovens normally required and at the same time reducing the emission of CO2. Thus, in a preferred embodiment, the gaseous depolymerization product of the process of the present disclosure is a product of the general formula C, based on the total weight of the gaseous depolymerization product after step (e) of the process of the present disclosure. n H 2n The content of the compound (n=2 to 4) (olefin) is at least 50% by weight, preferably at least 60% by weight, more preferably at least 65% by weight, most preferably at least 70% by weight, and particularly preferably at least 75% by weight.

[0100] The gaseous depolymerization products may contain small amounts of HCl, HCN, H2S, H2O, NH3, COS, etc., which can be optionally separated in a purification step before being introduced into the downstream segments of the steam cracker.

[0101] The present disclosure is further explained with reference to the figures and examples provided below.

[0102] drawing

[0103] FIG. 1 shows a flow chart of a process according to an embodiment of the present disclosure. In the process 500, a waste stream 502 is sorted to separate the polymer waste from unwanted materials and is optionally mechanically and / or chemically pretreated 504 to produce a polymer waste feedstock 506. The polymer waste feedstock 506 is then mixed with a catalyst 508 and subjected to catalytic pyrolysis to depolymerize 510 the polymeric material. The depolymerization of the polymeric material produces a gaseous product 520, a liquid product 530, and a solid product 540. The products are separated from each other, and optionally the gaseous product 520 and the liquid product 530 are further processed. The solid product 540 can also be further processed to separate char resulting from the depolymerization from the catalyst 508. The recovered catalyst can then be used in a subsequent iteration of the process.

[0104] FIG. 2 shows a flow chart of a process according to an embodiment of the present disclosure. In the process 600, polymer waste 605 is mixed with a catalyst 610 to form a mixture and sent to a first pyrolysis reactor 615. In the first pyrolysis reactor 615, the mixture is heated to depolymerize at least a portion of the polymer waste. After removing unwanted solids and char 625 produced in the first pyrolysis reactor, the remaining mixture is transferred to a second pyrolysis reactor 620. In the second pyrolysis reactor 620, the remaining mixture is heated again to depolymerize the remaining polymer waste. The gas 645 produced during depolymerization is sent to a steam cracker (not shown) and the liquid and wax 640 can be directed for further processing. EXAMPLES

[0105] The following analytical methods were employed:

[0106] 1) GC MS was used for liquid and gas analysis.

[0107] 2) After decoking the reactor residue at 800°C, the char residue was determined by mass balance.

[0108] 3) The liquid content was characterized using simulated distillation (SimDist) analysis according to ASTM D 7213:2012. The final boiling point (FBP), boiling temperature at 50%, and initial boiling point (IBP) are obtained from SimDist.

[0109] 4) The total content of unsaturated components in the liquid condensate was characterized by bromine number measurement using an 848 Titrino Plus (Metrohm AG, Herisau, Switzerland) equipped with a double PT-wire electrode integrated with a PT1000 temperature sensor and a 10 mL burette, according to ASTM D1159-01 described in Metrohm Application Bulletin 177 / 5e (December 2018). The bromine number (BrNo.) indicates the amount of bromine in grams absorbed by 100 g of sample.

[0110] 5) 1H-NMR analysis was performed by dissolving a sample of the liquid condensate in CDCl3 and characterizing the sample using proton NMR spectroscopy. Aromatic, olefinic, and aliphatic protons were assigned according to the chemical shifts summarized in Table 1.

[0111] [Table 2]

[0112] The olefinic proton types listed are assumed to correspond to the following structures: [ka]

[0113] The amounts of aromatic, olefinic and aliphatic protons may be determined based on the assigned peak integrals according to the following formula: Mole% of aromatic protons = [(I1+I2) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]% Mole% of olefin proton type 1=[(I4+I7) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]% Mole% of olefin proton type 2=[(I3+I5) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]% Mole% of olefin proton type 3=[(I6) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]% Mole% of olefin proton type 4=[(I8) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]% Molar % of paraffin protons = [(I9) / (I1+I2+I3+I4+I5+I6+I7+I8+I9)]%

[0114] 6) The moisture content of the catalysts was measured at 180 °C on 0.5–1 g samples using a Sartorius MA45 (Sartorius AG, Goettingen, Germany).

[0115] 7) To determine the pH value of the hydrodepolymerization product, a liquid sample of the hydrodepolymerization product was extracted with water at a water:sample volume ratio of 1:5, and the pH value of the aqueous solution was measured.

[0116] 8) Particle size distribution of particulate non-porous supports and catalysts was determined by Coulter Counter analysis according to ASTM D4438.

[0117] 9) The characteristics of the organic waste materials used were determined as follows:

[0118] Because the composition of organic waste materials can vary, 20-100 g samples of polymer waste were ground and analyzed. Alternatively, pelletized samples of polymer waste were analyzed. The following method was used.

[0119] i) Total Volaty (TV) was measured as the weight loss of a 10 g sample after 2 hours at 100° C. and 200 mbar.

[0120] ii) The water content was determined by Karl Fischer titration using a Metrohm 915 KF Ti-Touch instrument equipped with a PT100 indicator electrode for KF volumetric titration according to Metrohm Application Bulletin 77 / 3e in accordance with ASTM E203.

[0121] iii) IR spectroscopy was used to qualitatively identify different polymers (PP, PE, PS, PA, PET, PU, ​​polyester) and additives such as CaCO3.

[0122] iv) Standard elemental analysis was used to determine the weight % of H, C, N (DIN51732:2014-07) and S (tube furnace, ELTRA GmbH, Haan, Germany, DIN51724-3:2012-07).

[0123] v) 1H-NMR was used to determine the composition of polymers soluble in a solvent suitable for recording 1H-NMR spectra, i.e. PE / PP balance (including copolymers), PET, PS.

[0124] vi) Ash content analysis of plastics was determined at 800°C according to DIN EN ISO3451-1(2019-05).

[0125] vii) The bulk density of the polymer waste was determined according to DIN 53466.

[0126] viii) Corrosivity was measured as the pH value of the aqueous solution after a contact time of 3 hours (5 g of sample in 50 mL of distilled water).

[0127] ix) Quantitative elemental measurements (total chlorine content, Si or metal content) were performed using inductively coupled plasma atomic emission spectroscopy (ICP-AES).

[0128] x) Determine the ash content of liquid feedstocks such as pyrolysis oil in accordance with ASTM D482-19.

[0129] Various catalysts were prepared and tested in the depolymerization of various polymer wastes. The particulate non-porous support used in the catalysts was sand with a particle size distribution as summarized in Table 2, with 99% of the particles being less than 3 mm. Prior to use in the formation of the catalysts, the sand was pre-dried at 80 °C for 24 h in a drying oven with circulating air.

[0130] [Table 3]

[0131] Comparative Example:

[0132] Comparative catalysts were formed by mixing the acidic compound with 25 kg of the above sand to obtain the comparative catalysts shown in Table 4 (Comparative Example-1, Comparative Example-2, and Comparative Example-3).

[0133] Examples of the present disclosure:

[0134] A catalyst of the present disclosure using a mineral oil coating was prepared as follows.

[0135] 25.0 kg of sand was placed in a 60 L steel barrel with a screw cap and Teflon inlay. 350 mL of mineral oil was added (corresponding to 1.4 wt.% on sand). The drum was placed in a drum hoop mixer and rotated (approx. 100 rpm) for 1 h. 24.5 kg of the resulting mixture was placed in another drum and 500 g of the corresponding acidic component (corresponding to 2 wt.% loading) was added. The drum was placed in a drum hoop mixer and rotated (approx. 100 rpm) for 1 h. At the end of the mixing process, a well-flowing catalyst was obtained with particles of acidic component uniformly distributed on the surface of the sand particles.

[0136] The mineral oil used was Ondina X 432, available from Shell, and had the following characteristics:

[0137] [Table 4]

[0138] A catalyst of the present disclosure using a silica hydrogel coating was prepared as follows.

[0139] 25.0 kg of sand was placed in a 60 L steel barrel with a screw cap and Teflon inlay. 500 mL of water (corresponding to 2.0 wt.% relative to the sand) was added and the drum was placed in a drum hoop mixer and rotated (approximately 100 rpm) for 1 h. 24.5 kg of the resulting mixture was placed in another drum and 1000 g of a 1:1 milled free-flowing mixture of silica hydrogel and acidic compound (corresponding to a loading of 2 wt.%) was added. The drum was placed in a drum hoop mixer and rotated (approximately 100 rpm) for 1 h. At the end of the mixing process, a well-flowing catalyst was obtained with particles of acidic compound uniformly distributed on the surface of the sand particles. The resulting mixture was dried under vacuum at 120 °C for 6 h.

[0140] Silica hydrogel was prepared according to the procedure described in Example 1 of EP 1290042. The solids content of the hydrogel samples was 20 wt%. The D50 of the ground mixture of silica hydrogel and acidic components was 80-100 μm according to ASTM D4438.

[0141] Table 4 summarizes the catalysts used and the amounts of acidic compounds relative to the sand (unit: weight %).

[0142] [Table 5] Acidic compounds:

[0143] Zeolite CFG-1, Zeolyst ZSM-5, and Zeolyst Beta (CP811E-75) available from PQ Corporation (Malvern, PA, USA)

[0144] Siral40HPV: Si / Al mixed oxide of Al2O3 / SiO2 60 / 40[%] available from Sasol Germany GmbH (Hamburg, Germany).

[0145] Raw materials:

[0146] Some of the following organic waste materials were used as raw materials:

[0147] A: Pelletized agricultural and industrial packaging films.

[0148] B: Shredded flakes and small pieces of film.

[0149] C: Compressed flakes, fluff, and small pieces of film.

[0150] D: Shredded film.

[0151] E: Shredded and pelletized multilayer film.

[0152] G) 50 / 50 PE / PP blend virgin polymer in pellet form.

[0153] H) Shredded plastic waste fraction from end-of-life vehicles containing metal impurities.

[0154] Feedstock properties averaged from the three sample analyses are summarized in Table 5.

[0155] [Table 6] * ) Other contents include inorganic, polymeric or organic foreign matter and volatile components.

[0156] Ash: Ash content

[0157] TV: Total Volatile Matter

[0158] BD: Bulk density

[0159] Cl: Total chlorine content

[0160] PE: Polyethylene content

[0161] PP: Polypropylene content

[0162] PET: Polyethylene terephthalate content

[0163] PS: Polystyrene content

[0164] PA: Polyamide content

[0165] Other Content: Content of other impurities

[0166] The feedstock and catalyst were introduced into a reactor apparatus equipped with a heating unit, a gas discharge unit, a solid discharge unit, a condenser, and a screw for homogeneously mixing the reactor contents during depolymerization. The conditions of the depolymerization carried out are summarized in Table 6. The gaseous fraction obtained is further separated by condensation into liquid and gaseous depolymerization products. The amounts of the fractions obtained are also shown in Table 6.

[0167] [Table 7] (a) Anything less than 100% is due to losses

[0168] * ) A large amount of wax suspended in a heterogeneous liquid

[0169] ** ) % wax: product that is solid at room temperature

[0170] Referring to the results in Table 6, it can be seen that comparative runs #2-#5 showed unstable depolymerization with peaks of gas evolution corresponding to a black / brown liquid with a significant amount of wax suspended in it. This indicates that both thermal decomposition and catalytic depolymerization were occurring simultaneously. Even though run #5 was performed at a 50°C lower temperature compared to run #2, the amount of wax produced was much higher.

[0171] Catalysts 1, 2, and 3 with the coating agents allowed smooth experiments (Experiments #6–#9) with constant gas evolution at low temperatures, resulting in a homogeneous, transparent, yellow-brown liquid.

[0172] The resulting liquid and gaseous depolymerization products were further analyzed. The results of the analysis of the liquid depolymerization products are summarized in Table 7.

[0173] [Table 8] 1-H NMR has been used to obtain the mole % of aromatic, olefinic, and aliphatic protons in a sample. * ) Final boiling point (FBP), boiling temperature at 50%, and initial boiling point (IBP) are taken from SimDist.

[0174] As can be clearly seen from the data provided, depolymerization of waste polymers using the catalysts of the present disclosure yielded large amounts of liquefiable products with low aromatic and olefin content.

[0175] In another series of tests, different feedstocks were depolymerized to show that for a given feedstock, the catalysts disclosed herein can increase the proportion of gaseous fraction in the depolymerization reaction compared to pure thermal depolymerization (Run 11) and the comparative catalyst. The process parameters and mass balance of the obtained depolymerized products are summarized in Table 8.

[0176] [Table 9] (a) Any amount less than 100% is due to losses. (b) A large amount of wax suspended in a heterogeneous liquid. +) The liquid is a combination of all fractions and may contain waxy solid particles and aggregates, which disappear when heated above 50°C. *) Catalysts that maintained good selectivity after three successive runs were then regenerated by heating in air to 800°C and sieving off smaller particles (ash) below 500 μm. The above data show that the catalysts of the present disclosure are capable of producing large amounts of gaseous depolymerization products and maintaining good performance even when heterogeneous materials are added to the feedstock. It is further shown that the catalysts of the present disclosure can be effectively regenerated, thereby potentially enhancing the sustainability of the process.

[0177] The analytical results of the gaseous depolymerization products are summarized in Table 9.

[0178] [Table 10] *) Catalysts that maintained good selectivity after three consecutive runs were then regenerated by heating in air to 800°C and sieving to remove smaller particles (ash) below 500 μm. HC: Hydrocarbons Olefins: Sum of ethylene, propylene and butenes Olefins / HC: Ratio of total olefins to total hydrocarbons

[0179] As can be seen from Table 9, the disclosed process and catalysts produced gaseous depolymerization products containing large amounts of monomers useful as feedstocks for polymerization after purification. Any gaseous saturated hydrocarbons can be treated in the usual manner and returned to the steam cracker oven. In contrast, pyrolysis does not show selectivity to olefins and produces large amounts of methane, as reflected in Run #11.

Claims

1. A catalyst for the depolymerization of polymer waste, comprising as an active ingredient an acidic compound which is deposited on a particulate non-porous support with the aid of a coating agent.

2. 2. The catalyst of claim 1, wherein the particulate support is selected from the group consisting of sand, glass beads and metal particles.

3. Catalyst according to claim 2, wherein the support has a mean particle size D50, determined according to sieve analysis according to ISO 3310-1 / ASTM E11, of 0.2 to 20 mm, preferably 0.5 to 10 mm.

4. The catalyst of claim 3 wherein the support is sand.

5. The acidic compound is an Al / Si mixed oxide, Al 2 O 3 Catalyst according to any one of claims 1 to 4, characterized in that it is selected from the group consisting of aluminosilicates, silicas and zeolites.

6. Catalyst according to any one of claims 1 to 5, characterized in that the active compound is contained in the catalyst in an amount of 0.5 to 6% by weight, preferably 2 to 4% by weight, based on the total weight of the catalyst.

7. The catalyst according to any one of claims 1 to 6, characterized in that the coating agent is selected from the group consisting of oils, inorganic hydrogels, or combinations thereof.

8. 8. The catalyst according to any one of claims 1 to 7, characterized in that the coating agent is in the range of 1 to 300% by weight, preferably 2 to 150% by weight, more preferably 5 to 100% by weight, based on the amount of acidic compound.

9. A process for the depolymerization of polymer waste, the process comprising: (a) providing a raw material of polymer waste; (b) mixing said feedstock with the catalyst according to any one of claims 1 to 8; (c) pyrolyzing the mixture; (d) collecting the gaseous fraction produced during pyrolysis; (e) separating the collected gaseous fraction to obtain a gaseous depolymerization product and a liquid depolymerization product.

10. 10. The process of claim 9, further comprising distilling the liquid depolymerization product.

11. 11. The process according to claim 9 or 10, characterized in that the polymer waste consists of or comprises a plastic material selected from the group comprising or consisting of polyethylene (PE), polypropylene (PP), polystyrene (PS), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polyamide (PA), polyurethane (PU), polyacrylonitrile (PAN), and polybutylene (PB) and mixtures thereof.

12. 12. The process according to any one of claims 9 to 11, characterized in that the gas content in the depolymerization product after step (e) is preferably more than 30 wt.-%, more preferably more than 50 wt.-%, in particular more than 70 wt.-%, based on the combined weight of the gaseous depolymerization product and the liquid depolymerization product.

13. The gaseous depolymerization product may be a compound having the general formula C, based on the total weight of the gaseous depolymerization product after step (e) of the process of the present disclosure. n H 2n 13. The process according to any one of claims 9 to 12, characterized in that the content of compounds (n=2 to 4) is at least 50% by weight, preferably at least 60% by weight, in particular at least 65% by weight.

14. 14. The process according to any one of claims 9 to 13, characterized in that the depolymerization catalyst is separated from any solid content remaining after the depolymerization process and reintroduced into the process.

15. 15. The process of claim 14, wherein the catalyst is reactivated by heating before being reintroduced into the process.

Citation Information

Patent Citations

  • Upgrading hydrogen deficient streams using hydrogen donor streams in a hydropyrolysis process

    CN106795443A

  • Catalyst for cracking and polymerizing of waste plastic and waste grease and preparation process thereof

    CN1789375A

  • Method for protecting a F-T catalyst support by coating with a wax

    EP2000206A1

  • Method for chemically reusing plastics

    JP1993345894A

  • Decomposition catalyst

    JP2005205312A